Denitrifying Bioreactors for Nitrate Removal: A Meta‐Analysis. Issue 3 (1st May 2016) - Addy, Kelly; Gold, Arthur J.; Christianson, Laura E.; David, Mark B.; Schipper, Louis A.; Ratigan, Nicole A.
Abstract : Meta‐analysis approaches were used in this first quantitative synthesis of denitrifying woodchip bioreactors. Nitrate removal across environmental and design conditions was assessed from 26 published studies, representing 57 separate bioreactor units (i.e., walls, beds, and laboratory columns). Effect size calculations weighted the data based on variance and number of measurements for each bioreactor unit. Nitrate removal rates in bed and column studies were not significantly different, but both were significantly higher than wall studies. In denitrifying beds, wood source did not significantly affect nitrate removal rates. Nitrate removal (mass per volume) was significantly lower in beds with <6‐h hydraulic retention times, which argues for ensuring that bed designs incorporate sufficient time for nitrate removal. Rates significantly declined after the first year of bed operation but then stabilized. Nitrogen limitation significantly affected bed nitrate removal. Categorical and linear assessments found significant nitrate removal effects with bed temperature; a Q 10 of 2.15 was quite similar to other studies. Lessons from this meta‐analysis can be incorporated into bed designs, especially extending hydraulic retention times to increase nitrate removal under low temperature and high flow conditions. Additional column studies are warranted for comparative assessments, as are field‐based studies for assessing in situ conditions, especially in aging beds, with careful collection and reporting of design and environmental data. Future assessment of these systems might take a holistic view, reviewing nitrate removal in conjunction with other processes, including greenhouse gas and other unfavorable by‐product production. Core Ideas: Denitrifying beds may reduce water quality degradation and treat onsite wastewaters. Extending HRT can help manage nitrate under low temperatures and high flows. Multiyear laboratory column and in‐field bed assessments are needed to refine designs.